2014
DOI: 10.1097/nmd.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Abuse in Childhood Is a Differential Factor for the Development of Depression in Adults

Abstract: We evaluate the association between subtypes of early life stress (ELS; sexual abuse, physical abuse, emotional abuse, physical neglect, and emotional neglect) and psychiatric disorders in adults. The sample was composed of 81 adult psychiatric patients treated at the Day Hospital Unit in Brazil. The patients were assessed using the Mini International Neuropsychiatric Interview according to diagnostic criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. The presence of ELS was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 79 publications
7
47
0
13
Order By: Relevance
“…19 Experiencing verbal abuse throughout childhood was frequently self-reported, and was significantly associated with adult psychological distress. 18 In another recent study with a sample involving distinct psychiatric disorders, Martins et al 20 found that EA, among different types of early life stresses, was positively associated with psychopathology in adulthood, especially with mood disorders. Patients with a history of EA had higher severity scores for all symptoms, such as depression, hopelessness, suicidal ideation, anxiety, and impulsivity.…”
Section: Psychological Implicationsmentioning
confidence: 99%
“…19 Experiencing verbal abuse throughout childhood was frequently self-reported, and was significantly associated with adult psychological distress. 18 In another recent study with a sample involving distinct psychiatric disorders, Martins et al 20 found that EA, among different types of early life stresses, was positively associated with psychopathology in adulthood, especially with mood disorders. Patients with a history of EA had higher severity scores for all symptoms, such as depression, hopelessness, suicidal ideation, anxiety, and impulsivity.…”
Section: Psychological Implicationsmentioning
confidence: 99%
“…Corroborando com os achados da literatura, a pesquisa realizada por Martins et al 57 identificou associação entre o abuso emocional infantil e ocorrência de depressão na vida adulta de pacientes em regime de semi-internação psiquiátrica. Além disso, a literatura cientifica aponta que pacientes com EP apresentam pior resposta terapêutica.…”
Section: Transtornos De Adaptaçãounclassified
“…De acordo com estudos realizados previamente por nosso grupo de pesquisa e da literatura cerca de 70 a 80% dos pacientes com transtorno depressivo relataram a ocorrência de algum subtipo de estresse precoce (Carr, Martins, Stingel, Lemgruber, & Juruena, 2013;Martins et al 2011Martins et al , 2014Tunnard et al, 2013) Figura 3.1 -Esquema de distribuição da amostra total dos estudos realizados. …”
Section: Amostraunclassified
“…Considerando os subtipos de estresse precoce relacionados a maus tratos infantis, no nosso estudo encontramos com maior frequência casos de negligência e abuso emocional, seguidos por negligência física, abuso físico e, em último lugar, abuso sexual. Sendo assim, nossos resultados se assemelharam aos de Martins et al, 2014, que observaram maior prevalência relatos de abuso emocional, negligência física e emocional, contrastando com a menor porcentagem de maus tratos relacionados a abuso físico e abuso sexual entre pacientes psiquiátricos em regime de semi-internação. Cabe destacar que, dentre todos os subtipos de estresse precoce, identificamos uma menor prevalência de casos de abuso sexual e abuso físico entre os pacientes avaliados.…”
Section: Avaliação Das Correlações Entre O Temperamento Afetivo E As unclassified
See 1 more Smart Citation